Pedagogical Possibilities: A Review of Approaches to Undergraduate Teaching in Buddhist Studies - McGuire, Beverley (Religions, 2021)
This article presents a comprehensive review of the literature on teaching in Buddhist Studies within a framework of backward design, which begins by identifying our learning goals, then determining evidence of learning and planning course activities to facilitate such learning. It identifies big ideas in Buddhist Studies and transferrable skills that could serve as learning goals for our undergraduate courses. Finally, it concludes by suggesting future avenues of research about Buddhist pedagogy in the field of scholarship of teaching and learning.